Development of the Social Impact and Psychometrical Examination Scale - Eksi, Fusun; Okan, Nesrullah; Yilmazturk, Mucahit; Eksi, Halil (Istanbul Univ, Fac Letters, Dept Sociology, 2021)
The aim of this study is to develop a measurement tool for determining and psychometrically examining the social impact levels of university students. The scale is a 7-point Likert-type self-reported scale. The sample of the study consists of 316 students (235 females, 81 males; average age = 23.08 years) actively enrolled at various universities during the 2019-2020 academic year. As a result of the factor analysis, the scale has been determined to consist of 13 items and have a single-factor structure that explains 46.637% of the total variance. Cronbach's alpha of reliability for the scale is.941. For the item-total and item-remainder analyses, all values are significant at the level of p < .000. As a result of the analysis on the discriminatory power of the scale's total scores, a significant difference was determined to exist between the groups (p < .000). However, as a result of the confirmatory factor analysis, the goodness-of-fit values were seen to be within the appropriate reference ranges (chi(2) / df = 2.786; RMSEA = 0.076; SRMR = 0.09; CFI = 0.929; GFI = 0.915). The findings obtained as a result of the research reveal the Social Impact Scale (SIS) to be able to be used as a valid and reliable measurement tool in determining university students' social impact levels.
Keywords: Social impact; Adaptation; Scale development; Validity; Reliability